The Face of the Other in Home. Issue 1 (3rd April 2022) - Hu, Jun
Abstract: This essay investigates Toni Morrison's novel Home (2012) by focusing on the link between Frank Money, a battered African American veteran of the Korean War, and the young Korean girl he kills at the battlefield. Critics have not paid enough attention to the ethical appeal from the Korean girl to Frank. This essay argues that she plays a very important role in the recovery and growth of Frank, who has been haunted by her smiling face before her death. By drawing on the theories of Emmanuel Levinas and Judith Butler about the ethical demand made by the other, this essay aims to explore what lies in the vulnerable face of the Korean girl and what prevents Frank initially from responding to her ethically. The essay claims that the transformation of Frank depends not only on his ability to confront his crime of killing the Korean girl, but also to realize and respond to the ethical appeal from her, and finally in mourning the Korean girl, Frank allies with her in the shared vulnerability of all the others in the society.